2017
DOI: 10.1007/s00421-017-3584-2
|View full text |Cite
|
Sign up to set email alerts
|

Old adults preserve motor flexibility during rapid reaching

Abstract: PurposeOur ability to flexibly coordinate the available degrees of freedom allows us to perform activities of daily living under various task constraints. Healthy old adults exhibit subclinical peripheral and central nervous system dysfunctions, possibly compromising the flexibility in inter-joint coordination during voluntary movements and the ability to adapt to varying task constraints.MethodWe examined how healthy old (75.4 ± 5.2 years, n = 14) compared with young adults (24.3 ± 2 years, n = 15) make use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
0
12
2
Order By: Relevance
“…It was previously suggested that greater motor abundance will emerge in tasks with greater relative physical demand ( Greve, Hortobagyi & Bongers, 2017 ; Greve et al, 2013 ), which contradicts the present findings. It may be that the relationship between physical demand and motor abundance is non-linear with potentially plateauing effects.…”
Section: Discussioncontrasting
confidence: 99%
“…It was previously suggested that greater motor abundance will emerge in tasks with greater relative physical demand ( Greve, Hortobagyi & Bongers, 2017 ; Greve et al, 2013 ), which contradicts the present findings. It may be that the relationship between physical demand and motor abundance is non-linear with potentially plateauing effects.…”
Section: Discussioncontrasting
confidence: 99%
“…It was previously suggested that greater motor abundance will emerge in tasks with greater relative physical demand (Greve et al 2017;Greve et al 2013), which contradicts the present findings. It may be that the relationship between physical demand and motor abundance is nonlinear with potentially plateauing effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Wang et al reported that older adults have preserved muscle motor abundance but were more delayed at their recruitment during rapid balance recovery, than younger adults (Wang et al 2017). The tasks used by Greve and Colleagues were either much slower, or required a combination of low muscular force and fast movement speed (Greve et al 2017;Greve et al 2013). It is plausible that the speed-force demands in previous studies were low (Greve et al 2017;Greve et al 2013), such that muscle…”
Section: Discussionmentioning
confidence: 99%
“…Second, a suitable task-relevant performance variable that is affected by variations in the elemental variables also needs to be chosen for analysis [12,13]. Examples of performance variables stabilized by synergies include the position of the center of mass in transfer and standing tasks, hand position and orientation in reaching tasks, total force in finger pressing tasks [14][15][16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%